Determination of plasma parameters with a probing magnetic field pulse - Russkikh A. G. Aleksandr Gennadievich; Oreshkin V. I. Vladimir Ivanovich; Zhigalin A. S. Aleksandr Sergeevich; Yushkov G. Yu. Georgy Yurjevich (2016, 2016)
Title screen